Abstract Machine Geographical Information Systems (GIS) for literary and cultural studies: Mapping Kavanagh - TRAVIS, CHARLES (Edinburgh University Press, 2011)
Drawing upon previous theoretical and practical work in historical and qualitative applications of Geographical Information Systems (GIS), this paper, in Giles Deleuze and Felix Guattari's terminology, conceptualizes GIS as `an abstract machine? which plays a `piloting role? which does not `function to represent? something real, but rather `constructs a real which is yet to come.? To illustrate this digital humanities mapping methodology, the essay examines Irish writer Patrick Kavanagh's novel The Green Fool (1938) and epic poem The Great Hunger (1946) and their respective contrasting topophilic and topophobic renderings of landscape, identity and sense of place under the lens M.M. Bakhtin's `Historical Poetics? (chronotope) to illuminate GIS's ability to engage in spatio-discursive visualization and analysis. The conceptualizations and practices discussed in this paper reconsider GIS software/hardware/techniques as a means to engage subjects of concern to literary and cultural studies commensurate with the recent strong interest in the geographical and spatial dimensions of these cognate areas.
PUBLISHED. ? Edinburgh University Press and the Association for History and Computing 2011 www.eupjournals.com/ijhac. Edinburgh UP permits posting of the publisher's pdf on the author's departmental webpage upon acceptance for publication. In TCD fulltext links on School webpages are managed via TARA.
Keywords: Digital Humanities; Geographical Information Systems (GIS)